2013
DOI: 10.30539/ijvm.v37i2.1390
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical study on the effect of Toxoplasma gondii on Liver function in Women

Abstract: The aim of this study was to detect the effect of toxoplasmosis on some liver enzyme activity such as bilirubin concentration, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline Phosphatase (ALP) in serum. Twenty hundred and fifty women were examining by Enzyme-linked immunosorbent assay (ELISA). One hundred and thirty-four were infected with toxoplasmosis with different number of abortion (1-4) times were used in this work. All Serum ALT and AST activities were increased and ALP and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Toxoplasmosis causes severe and progressive damage to the liver (18,19), remarkable proliferations of organisms such damage in the liver metabolism (20).We found that liver enzymes activities ALP, AST, and ALT were increased in T. gondii-infected women, Serum AST and ALT activities are excellent markers of hepatocellular injury and serum ALT activity is more specific than serum AST for assessing liver injury and this results consistent with previous studies conducted on experimental animals (21,22,23). The significantly elevated serum activities of liver enzymes also agreed with (24). Increased plasma AST and ALT activities reflects impairment of the liver, where this infection can cause round cell infiltration in the portal areas, cholestasis, swollen endothelial cells and focal necrosis of liver cells (25).When the liver is impaired the liver cells release…”
Section: Discussionsupporting
confidence: 59%
“…Toxoplasmosis causes severe and progressive damage to the liver (18,19), remarkable proliferations of organisms such damage in the liver metabolism (20).We found that liver enzymes activities ALP, AST, and ALT were increased in T. gondii-infected women, Serum AST and ALT activities are excellent markers of hepatocellular injury and serum ALT activity is more specific than serum AST for assessing liver injury and this results consistent with previous studies conducted on experimental animals (21,22,23). The significantly elevated serum activities of liver enzymes also agreed with (24). Increased plasma AST and ALT activities reflects impairment of the liver, where this infection can cause round cell infiltration in the portal areas, cholestasis, swollen endothelial cells and focal necrosis of liver cells (25).When the liver is impaired the liver cells release…”
Section: Discussionsupporting
confidence: 59%
“…The results of the fatigue tester revealed the number of periods required to break the samples. The fatigue S-N curve is drawn by plotting a curve that reflects the experimental data of fatigue tests [42,43]. Figs.…”
Section: Fatigue Propertiesmentioning
confidence: 99%